2019
DOI: 10.1038/s42003-019-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell type phylogenetics informs the evolutionary origin of echinoderm larval skeletogenic cell identity

Abstract: The multiplicity of cell types comprising multicellular organisms begs the question as to how cell type identities evolve over time. Cell type phylogenetics informs this question by comparing gene expression of homologous cell types in distantly related taxa. We employ this approach to inform the identity of larval skeletogenic cells of echinoderms, a clade for which there are phylogenetically diverse datasets of spatial gene expression patterns. We determined ancestral spatial expression patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 109 publications
0
31
0
Order By: Relevance
“…We used this to test the hypothesis that changes in the expression pattern between H. erythrogramma and the ancestral GRN arose concurrently with accelerated development rather than as a difference in the Heliocidaris lineage from other planktotrophic sea urchins where the expression of these genes is well characterized. The T-box gene Tbr was restricted to the SM lineage in euechinoid urchins [51,69] rather than its ancestral role in pan-mesodermal and broad endomesoderm specification [38,60,65,70,71] but it remains indispensable to activate the normal endomesoderm GRN [72,73] and the replacement SM-GRN [47,74]. Tbr ’s placement in the GRN immediately downstream of the HesC/Pmar1 logic gate and integration into a circuit with Alx1 has been proposed as the key event in the evolution of the larval SM cell type [38,45,75].…”
Section: Resultsmentioning
confidence: 99%
“…We used this to test the hypothesis that changes in the expression pattern between H. erythrogramma and the ancestral GRN arose concurrently with accelerated development rather than as a difference in the Heliocidaris lineage from other planktotrophic sea urchins where the expression of these genes is well characterized. The T-box gene Tbr was restricted to the SM lineage in euechinoid urchins [51,69] rather than its ancestral role in pan-mesodermal and broad endomesoderm specification [38,60,65,70,71] but it remains indispensable to activate the normal endomesoderm GRN [72,73] and the replacement SM-GRN [47,74]. Tbr ’s placement in the GRN immediately downstream of the HesC/Pmar1 logic gate and integration into a circuit with Alx1 has been proposed as the key event in the evolution of the larval SM cell type [38,45,75].…”
Section: Resultsmentioning
confidence: 99%
“…We propose that the evolutionary change that linked alx1 activation to the prefertilization axis of the oocyte bypassed an ancestral mode of regulation that was based on VEGF signaling (Fig 10). The selective coexpression of vegf3 , vegfr-10-Ig , and alx1 in embryonic and adult skeletogenic centers in all echinoderms that have been examined strongly suggests that VEGF signaling had an ancient role in skeletogenesis and that expression of both vegfr-Ig-10 and alx1 was associated with the invention of skeletogenic cells very early in echinoderm evolution [4,68,66]. Although the evolutionarily derived, initial phase of alx1 expression in euechinoids is independent of VEGF signaling [11], vestiges of an ancestral regulatory mechanism may persist in the apparent, signal-dependent regulation of alx1 in the ventral domain of the PMC syncytium at the late gastrula stage [12].…”
Section: Discussionmentioning
confidence: 99%
“…The vegfr-Ig-10 gene is also expressed in adult skeletogenic centers, even in clades that lack a larval skeleton (Gao and Davidson, 2008;Morino et al, 2012). Other comparative studies in echinoderms have found a strict correlation between the expression of vegf3/vegfr-Ig-10 and the formation of an embryonic skeleton (Duloquin et al, 2007;Morino et al, 2012;Adomako-Ankomah and Ettensohn, 2013;Erkenbrack and Petsios, 2017;Erkenbrack and Thompson, 2019). Remarkably, human VEGFA is able to rescue skeleton formation in sea urchin embryos that lack endogenous Vegf3 expression (Morgulis et al, 2019).…”
Section: Vegf and Vegfrmentioning
confidence: 96%
“…With respect to echinoderms, considerable evidence supports the view that alx1 arose very early in echinoderm evolution through gene duplication, relatively quickly acquired a robust, biomineralization-related function, and was subsequently co-opted into the early embryo in echinoderm taxa that possess larval skeletons (echinoids and ophiuroids; Khor and Ettensohn, 2017;Shashikant et al, 2018). The biomineralizing cells of the ancestral echinoderm, which were likely of mesodermal origins, expressed alx1, ets1, erg, vegfr, and other components of a core skeletogenic program, as well as an assortment of more rapidly evolving biomineralization effector proteins (Gao and Davidson, 2008;Dylus et al, 2018;Erkenbrack and Thompson, 2019;Li et al, 2020). To draw inferences concerning the evolution of alx gene expression and function more deeply within Ambulacraria (echinoderms and hemichordates), it will be important to learn more about the single alx gene of hemichordates, including its pattern of expression, gene targets, and role in the formation of the small, calcareous skeletal elements of adult hemichordates (Cameron and Bishop, 2012) and to more precisely determine the embryological origins of the alx1-expressing cells of adult echinoderms, which are more relevant to the ancestral echinoderm condition than the more commonly studied larval forms.…”
Section: Alx Genes and The Evolution Of Deuterostome Biomineralizationmentioning
confidence: 99%